The Influence of Government Policies and Economic Factors on the Growth of Entrepreneurial Activities in Khartoum, Sudan - Babiker, Yusra H. M.; Timan, Elfadil; Ali, Malik Elnaeem Mohammed (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Understanding the influence of government policies and economic factors on the growth of entrepreneurial activities is considered a step towards successful entrepreneurship in Sudan. The goal of this article is to explore the government policies and economic factors which influence the growth of entrepreneurial activities in Khartoum Locality, Khartoum State, Sudan. The research was conducted on a sample of 400 national potential entrepreneurs, and data were collected using a structured questionnaire and personal interviews. Respondents are asked 43 questions to assess their perception of the main factors influencing the growth of entrepreneurial activities. The study adopted an analytical descriptive methodology whereby the data were processed by the statistical package for social sciences (SPSS). Percentages, frequencies, and hypothesis tests were used to analyze data. The study revealed that one major problem for entrepreneurs is the high tax fees which hinder the progress of entrepreneurship. Also, not everyone could get a business license. Furthermore, they tend to enter the field of entrepreneurship due to limited government employment opportunities. Entrepreneurs considered entrepreneurship as one of the best solutions for their unemployment problems. Through business incubators, entrepreneurship may expand and flourish in Sudan. Microfinance programs may contribute to the development of entrepreneurial activities, although entrepreneurs face obstacles in such programs, for example,<strong style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> <span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">the inability to pay back and the failure of their projects. Credit and loan policies towards entrepreneurs in commercial banks in Sudan need to encourage new ideas and innovations. Self-finance and family finance are important sources for getting money to execute entrepreneurial activities. The study recommends that government agencies should provide financing facilities for entrepreneurs in a way that may contribute to the development of entrepreneurial activities. The government of Khartoum State needs to concentrate more on entrepreneurial training as it is necessary to improve entrepreneurship. It is very important to decrease tax fees because it is a large obstacle facing entrepreneurs. The authorities must facilitate the provision of business licenses to those who have the ability and desire to establish a business. Commercial banks need to strengthen microfinance programs to help entrepreneurs to enter the entrepreneurship field.